2020
DOI: 10.1002/cssc.201903227
|View full text |Cite
|
Sign up to set email alerts
|

An Insoluble Anthraquinone Dimer with Near‐Plane Structure as a Cathode Material for Lithium‐Ion Batteries

Abstract: Figure 4. (a) CV curveso ft he BAQBc athode in the first cycle at as can rate of 0.1 mV s À1 and in ap otentialrange of 1.5-3.5 V; (b) corresponding galvanostatic discharge/charge profilesa t0.2 Cr ate (1 C = 218 mA g À1 )i nits first cycle;( c) cycling performance and Coulombic efficiency of AQ and BAQB at 0.2 C; (d) Nyquistp lots of BAQBa fter different cycles measured by in situ EIS;(e) rate capability and (f) galvanostatic discharge and chargep rofiles of BAQBa td ifferent currentd ensities.Figure 5. (a) R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…TAQB was synthesized using the previously reported palladium‐catalyzed Suzuki coupling reaction method. [ 57 ] Under the protection of nitrogen atmosphere, 2‐bromoanthraquinone (AQBr) (1.13 g, 3.94 mmol), 1,3,5‐ tris (4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolan‐2‐yl)benzene (TTDB) (0.50 g, 1.52 mmol), K 2 CO 3 (0.76 g, 5.50 mmol), and Pd 0 (PPh 3 ) 4 (0.13 g, 0.11 mmol) were added in a fully dried Schlenk flask. Then 40 mL toluene and 6 mL methanol were added into the flask and the mixture was stirred at 90 °C under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…TAQB was synthesized using the previously reported palladium‐catalyzed Suzuki coupling reaction method. [ 57 ] Under the protection of nitrogen atmosphere, 2‐bromoanthraquinone (AQBr) (1.13 g, 3.94 mmol), 1,3,5‐ tris (4,4,5,5‐tetramethyl‐1,3,2‐dioxaborolan‐2‐yl)benzene (TTDB) (0.50 g, 1.52 mmol), K 2 CO 3 (0.76 g, 5.50 mmol), and Pd 0 (PPh 3 ) 4 (0.13 g, 0.11 mmol) were added in a fully dried Schlenk flask. Then 40 mL toluene and 6 mL methanol were added into the flask and the mixture was stirred at 90 °C under nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…An anthraquinone dimer, 1,4-bis(9,10anthraquinonyl)benzene (BAQB) (6) can be formed through C-C single bonds while maintaining low steric hindrance. 34 Such a molecular structure will remain relatively planar with small twist angles between adjacent aromatic rings, which the authors deemed a near-plane structure. The main advantage of this near-planar molecular design of anthraquinone dimers is that the intermolecular π-π stacking is enhanced, resulting in the formation of insoluble BAQB.…”
Section: Chemical Modification At the Molecular Levelmentioning
confidence: 99%
“…Yang et al demonstrated another clever approach to address the dissolution issue on anthraquinone derivatives. An anthraquinone dimer, 1,4‐bis(9,10‐anthraquinonyl)benzene (BAQB) ( 6 ) can be formed through C–C single bonds while maintaining low steric hindrance 34 . Such a molecular structure will remain relatively planar with small twist angles between adjacent aromatic rings, which the authors deemed a near‐plane structure.…”
Section: Chemical Modification Of the Electrode Materialsmentioning
confidence: 99%
“…[ 19 ] Especially, as one of the n‐type carbonyl compounds, anthraquinone shows a high theoretical capacity (260 mAh g −1 ), suitable redox potential, and fast two‐electron redox kinetics, making it one of the most attractive cathode materials. [ 20 ] However, just like other organic electrode materials, anthraquinone also suffered from low rate performances, rapid capacity decay, and short cycle life due to the poor conductivity and undesirable dissolution in organic electrolytes. [ 21–23 ] For example, the anthraquinone shows an initial specific capacity of 193 mAh g −1 and a fast capacity degradation with only 14 mAh g −1 remained after 100 cycles.…”
Section: Introductionmentioning
confidence: 99%